2020
DOI: 10.1016/j.jgr.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 attenuates microglial activation against toxoplasmic encephalitis via TLR4/NF-κB signaling pathway

Abstract: Background Ginsenoside Rh2 (GRh2) is a characterized component in red ginseng widely used in Korea and China. GRh2 exhibits a wide range of pharmacological activities, such as anti-inflammatory, antioxidant, and anticancer properties. However, its effects on Toxoplasma gondii ( T. gondii ) infection have not been clarified yet. Methods The effect of GRh2 against T. gondii was assessed under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
1
22
0
1
Order By: Relevance
“…We evaluated the cytotoxicity of representative compounds 20 e (MIC 50 =0.46 μM) and 21 a (MIC 50 =0.31 μM) by 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT) assay [46–49] . Considering the frequent external use of antifungal agents, we used the human foreskin fibroblast‐1 (HFF‐1) cell line.…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated the cytotoxicity of representative compounds 20 e (MIC 50 =0.46 μM) and 21 a (MIC 50 =0.31 μM) by 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide (MTT) assay [46–49] . Considering the frequent external use of antifungal agents, we used the human foreskin fibroblast‐1 (HFF‐1) cell line.…”
Section: Resultsmentioning
confidence: 99%
“…As medicinal herbs have been widely studied for its anti-inflammatory properties [ 20 , 21 ], we desire to investigate effective medicinal herbs that have potent medicinal properties. Phellinus baumii has long been used as herbal medicine in Asia, particularly China, Korea, and Japan for the treatment of a variety of ailments, including diabetes, hypercholesterolemia, and most notably cancer [ 11 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…38 A large number of our previous studies have shown that SD-Na has a good anti-T. gondii activity in vivo. 9,39,40 Therefore, we used SD-Na as the positive control drug in vivo. Sertraline hydrochloride (SERT, HY-B0176A)…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
“…Apart from N group cells, other cells were infected with T. gondii (parasite:cell = 5:1) in medium. 39 After 4 h, T. gondii-infected BV2 cells were washed with medium to remove extracellular parasites and then were based on the above drug intervention 36 h later, 39 the cells were further processed for subsequent experiments.…”
Section: In Vitro Experiments Protocolmentioning
confidence: 99%
See 1 more Smart Citation